Decision support system for costing TADS in an Indian modular switches manufacturing organisation. (1st January 2011) - Vinodh, S.; Prasanna, M.; Manoj, S.
The manufacturing organisations have been witnessing a transition in the manufacturing paradigm due to increasing competition. The manufacturing paradigm was shifted from craft to mass manufacturing and then mass customised manufacturing. Agile manufacturing (AM) is an advanced manufacturing paradigm that enables organisations to survive in the competitive environment. The traditional costing method could not be applied to the AM systems. Researchers have recommended certain methods for costing expenses associated with AM practices. This paper reports a project that uses the cost data, pertaining to activity-based costing (ABC) of an advanced AM system called total agile design system (TADS). Since the computation of cost data produced manually is time-consuming and errorprone, a decision support system (DSS) has been developed. This DSS is referred to as DSS–TADS–ABC. The experiences gained on the design and development of DSS–TADS–ABC is presented in this paper.